Оptimal algorithm of radio brightness estimation in the spatial distributed radiometric sys-tems - Volosyuk, V.K.; Zhyla, S.S.; Pavlikov, V.V.; Abramov, A.D.; Yakovlev, V.G. (Radiotekhnika, 2017)
Optimization of processing of radio thermal radiation noise processes in multichannel spatially-distributed radiometric systems is performed. The received algorithms applicable in the systems of aperture synthesis are received within the maximum likelihood method in the assumption that spectral brightness of radiation within the frequency band of the receiver is constant, but as the image of a radiating object it depends on spatial (angular) coordinates. Feature of the solved tasks consists in using spectral VF -transforms which do not require execution of the spatiotemporal band-limitedness (quasi monochromatic approximation) condition and make it possible to solve the problem of synthesis of algorithms for processing wideband and ultra wideband processes.